(untitled) (International Journal of Environmental Sciences, 2025)
Strontium silicate-based phosphors (Sr₂SiO₄:Eu²⁺, Dy³⁺) are promising materials for next-generation white light-emitting diodes (WLEDs) due to their strong green emission, high thermal stability, and tunable luminescent properties. This paper presents a detailed study of the synthesis, structural, morphological, and optical characteristics of Sr₂SiO₄:Eu²⁺, Dy³⁺ phosphors prepared via the sol-gel technique. Comprehensive characterization was performed using X-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), Fourier-transform infrared spectroscopy (FTIR), and photoluminescence (PL) spectroscopy. The sol-gel route yielded highly crystalline, uniformly dispersed, and efficiently luminescent phosphors, demonstrating its potential for scalable optoelectronic applications.